O-027 Small extracellular vesicle (sEV) protein cargo as potential biomarker for endometriosis. (30th June 2022) - Nazri, H; Heilig, R; Fischer, R; Kessler, B; Subramaniam, K; Becker, C; Tapmeier, T
Abstract: Study question: Can an endometriosis-specific protein signature in small extracellular vesicles (sEV) from peritoneal fluid (PF) be utilised as a non-invasive biomarker of the condition? Summary answer: Yes, potentially. We found differences in the concentrations and protein cargo of PF-derived sEV between controls and endometriosis samples, most notably in CD44 expression. What is known already: Endometriosis, defined as endometrial-like tissue outside the uterus, causes pain and/or subfertility in 10% of reproductive age women. The cause is unknown, resulting in inadequate diagnostic methods and treatment options. There is no clinically relevant biomarker for endometriosis yet. Small extracellular vesicles (sEV), produced by virtually every cell, have been described in diseases such as cancer, diabetes, and pre-eclampsia, and could similarly be important in endometriosis. We previously identified sEV in PF of women with endometriosis, and here investigated the protein cargo of PF sEV as biomarker of the disease. Study design, size, duration: PF samples were obtained from participants in the ENDOX study, Endometriosis CaRe Centre, Nuffield Department of Women's and Reproductive Health, University of Oxford (REC ref. 09/H0604/58) according to WERF EPHect standards. Women between 18-49 years of age (n = 63) who had undergone diagnostic laparoscopy were classified according to cycle phase (proliferative/secretory/menstrual) and severity of endometriosis (ASRM stages I+II or stages III+IV). Exclusion criteria were hormonal treatment, malignancy, pregnancy, breastfeeding, and inability to understand the consent form. Participants/materials, setting, methods: The participant groups were control proliferative, n = 7; control secretory, n = 9; control menstrual, n = 3; StI+II proliferative, n = 8; StI+II secretory, n = 10; St1+II menstrual, n = 7; StIII+IV proliferative, n = 5; StIII+IV secretory, n = 11; StIII+IV menstrual, n = 3. 1 mL PF was centrifuged to remove cells, debris, and microvesicles. sEV were isolated using size exclusion chromatography (SEC) and analysed by nanoparticle tracking analysis (NTA), immunoblotting, and mass spectrometry (LC-MS/MS). Main results and the role of chance: We confirmed the presence of exosomes in PF from women at different stages of endometriosis and from disease-free patients at different menstrual cycle phases by NTA, immunoblotting and mass spectrometry. Enriched sEV were positive for ALIX, CD9, and syntenin. The mode size of PF particles from women with endometriosis was 115 ± 15.5 nm, whereas in non-endometriotic women it was 95 ± 17.3 nm (n.s.). sEV concentrations were higher in endometriosis compared to controls, and highest in stage III-IV endometriosis, followed by stage I-II endometriosis and controls, irrespective of menstrual cycle phase (P = 0.0210). sEV concentration in stage III-IV endometriosis decreased consistent with a transition from proliferative to secretory phase. Likewise, PF-derived sEV numbers within stage I-II endometriosis samples increased, as these samples transitioned from proliferative to secretory cycle phases. Proteomic analysis showed distinct distribution patterns of proteins within endometriosis PF-derived sEVs compared to controls. Consistent with earlier studies, we found CD44 as an sEV protein uniquely within the endometriosis population and contributing significantly to the separation of endometriosis and control samples by the highest variable importance projection (VIP) score in our data set. Limitations, reasons for caution: The main limitation of this study is the small number of samples across the different groups, and the limited amount of PF per sample. Wider implications of the findings: PF-derived sEV differ between endometriosis and control patients. Concentrations vary regardless of cycle phase and disease stage, and this difference appears to be reflected in the proteomics analysis. The presence of CD44 within sEV could help diagnose endometriosis. Trial registration number: not applicable